Method for restoring PPG signals using ECG correspondences and SVR. Issue 24 (1st November 2013) - Kim, H.; Kim, Y.; Kim, J.; Lee, E.C.
Abstract : A novel method for restoring photoplethysmography (PPG) signals using electrocardiography correspondences and support vector regression (SVR) is proposed. To enhance the PPG quality, five correspondences between the period signals of PPG and ECG were automatically detected, and their position and amplitude are independently trained for defining the estimator. The result shows that the quality of the PPG signal restored using the proposed method is greatly enhanced and becomes similar to that of the ECG signal.